2019
DOI: 10.1007/s40273-019-00870-w
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab for the Treatment of Locally Advanced, Unresectable, Stage III Non-Small Cell Lung Cancer: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: As part of the Single Technology Appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer (AstraZeneca) of durvalumab (IMFINZI TM) to submit evidence for the clinical and cost effectiveness of durvalumab for the treatment of patients with locally advanced, unresectable, stage III non-small cell lung cancer whose tumours express programmed death-ligand 1 (PD-L1) on ≥ 1% of tumour cells and whose disease has not progressed after platinum-based chemoradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Numerous cost-effectiveness analyses have been published based on both the ITT and the PD-L1 TC ≥ 1% PACIFIC populations. These analyses report a lower range of QALY gains with durvalumab therapy (0.24-1.32 for the PD-L1 TC ≥ 1% population) compared with the original company base-case analysis (2.93) (Table 3 in the ESM) [30,31,[44][45][46][47][48]; this could be explained, in part, by the use of different modelling approaches, decision problems, and/or assumptions regarding long-term survival benefit. The recently published data from PACIFIC (March 2020 DCO) demonstrated a gain in median OS of 27.8 months with durvalumab therapy versus placebo and a sustained OS and PFS benefit with durvalumab at 4 years (PD-L1 TC ≥ 1% population) [34]; the 48-month OS rates were 55 and 38% with durvalumab and placebo, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous cost-effectiveness analyses have been published based on both the ITT and the PD-L1 TC ≥ 1% PACIFIC populations. These analyses report a lower range of QALY gains with durvalumab therapy (0.24-1.32 for the PD-L1 TC ≥ 1% population) compared with the original company base-case analysis (2.93) (Table 3 in the ESM) [30,31,[44][45][46][47][48]; this could be explained, in part, by the use of different modelling approaches, decision problems, and/or assumptions regarding long-term survival benefit. The recently published data from PACIFIC (March 2020 DCO) demonstrated a gain in median OS of 27.8 months with durvalumab therapy versus placebo and a sustained OS and PFS benefit with durvalumab at 4 years (PD-L1 TC ≥ 1% population) [34]; the 48-month OS rates were 55 and 38% with durvalumab and placebo, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The de novo base-case analysis used a state-transition modelling approach because evidence from PACIFIC indicated that the benefit of durvalumab was primarily driven by PFS [ 22 , 23 , 30 ], whereas post-progression survival (PPS) was similar between the durvalumab and placebo arms [ 30 ]. In the company base-case analysis, durvalumab therapy resulted in an expected gain of 2.93 quality-adjusted life-years (QALYs) compared with standard-of-care active follow-up (placebo), corresponding to a deterministic incremental cost-effectiveness ratio (ICER) of £19,366/QALY gained (after incorporating minor adjustments to correct errors identified by the NICE-commissioned evidence review group [ERG]) [ 30 , 31 ]. Therefore, this ICER fell below the £20,000–30,000/QALY gained willingness-to-pay threshold that NICE applies for cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have to do with limitations of the STM approach as discussed above, or the added complexity of implementing both approaches, or other barriers to implementing the TSD 19 recommendation. The ERG, having experienced similar difficulty in a previous STA [ 21 ], therefore argues that care should be taken to justify the employment of this recommendation and feels that perhaps TSD 19 may need further elaboration to detail in what specific cases validation of PSM with STM is indicated. The ERG so far has not seen any STA having successfully cross-validated a PSM by an STM alongside it—or the other way around.…”
Section: Key Methodological Issuesmentioning
confidence: 99%
“…To reflect real-world treatment of unresectable stage III NSCLC in the United States, 36.2% of patients in the cCRT-alone arm were assumed to receive subsequent consolidation with chemotherapy (paclitaxel 1 carboplatin, 33.9%; pemetrexed 1 cisplatin, 2.2%). 27 However, studies have shown that consolidation with chemotherapy does not improve survival 28 ; thus, it was assumed that these patients incurred no survival advantage.…”
Section: Costsmentioning
confidence: 99%